Pemberian Reinforcement Sebagai Upaya Mendisiplinkan Siswa Kelas III SD Pada Pembelajaran Daring - Fransisca Dara Kristina; Wiyun Philipus Tangkin (STKIP Andi Matappa Pangkep, 2022)
Problems that occur in the learning process will always exist. One of the problems that the authors found was the indiscipline of students in using hand signals. Discipline occurs when students do not obey the applicable rules. So, the teacher needs to apply a method that can overcome the problem of student indiscipline. Student indiscipline can be overcome by using the method of giving rewards. The aim of this research is to see the effect of the reinforcement method on student discipline in online learning. The research method that is used by the researcher is descriptive qualitative. The method of giving reinforcement can be used to discipline students, because the reinforcement can motivate students, so students will tend to repeat the same thing in the future. The suggestions for teachers are that teachers can apply reinforcement consistently so the teacher can see the consistency of changes in students' disciplinary attitudes. The suggestions for other researchers are to apply this method longer, so that this research can be more measurable and the pattern of changes in student behavior is more visible.